Qualidade de vida, direito fundamental uma questão urbana: a função social da cidade - Jampaulo Júnior, João (2007)
The subject of the present work refers to theme in the area of Constitutional Law. It includes the study of one of the main Fundamental Rights: the right to the life. This study is not about a double meaning as the right of remaining alive and the right of having a worthy life regarding surviving. It s about a triple meaning where we recognize the quality of life as a Fundamental Right.The Constitutional Text of 1988 associated the quality of life merely to the environment (art. 225). Analysing this constitutional dispositive and associating it with questions, as the principle of human dignity in its material sense, the quality of urban life, supportable development and supportable city, the following question was isolated: is only the environment essential to a healthy quality of life? After approaching situations as human life in the city since the an-cient times until the present, including passages as the urban phenomenun and the rural exodus, we face the present city, its way of life and its main problems. In this way, the social function of the city arises and also its importance in preserv-ing the quality of life as Fundamental Right. The Fundamental Rights begin to appear as the center of the work, and in special, through the immediate guarantee of its application. The Letter of 1988 doesn`t present taxable roll of Fundamental Rights. Searching in the Con-stitution for these rights we see that they are not enumerated due to several rea-sons. First, they present an incomplete and unfinished character. Second, it is due to the execution of the Constitution and it is also because of the picture of the constitutional mutation. In this way, the quality of life appears as Funda-mental Right due to a systemic interpretation of the Constitution, including the article 5o (right to the life), the article 225 (environment as essential to the healthy quality of life) and it is also due to the inclusion of paragraph 2º of art. 5o of the Major Law. The theme is named Quality of life: Fundamental Right A urban question: the social function of the city . It deals with the quality of life in the city as a new Fundamental Right showing its requirements. The social functions of the city gain a larger vision, without forgetting its four general functions (habita-tion / work / circulation / recreation).The fair distribution of public services is an instrument to guarantee the right to the quality of life, as well as it s necessary mechanisms to eradicate proverty and marginal life and the reduction of social and regional inequalities.Presenting the existent concepts about quality of life, it is offered one proposal of concept about the third meaning of the right to the life, according to the optics of the present work. To finish it is emphasized citizenship as another instrument of search and defence of the right to the quality of life. The purpose is to defend the quality of life as a Fundamental Right and not only one right associated to the environment. It is focused the life in the city (urban question). For this purpose, it is essential the reading and the analysis of the problem on a scientific prism. The intention was not to exhaust the subject, but only to investigate and demonstrate with a major deep examination the cho-sen theme through a more critic and objective reflection